Excise Tax Charts - FRED PANZER (Tufts Archival Research Center, 2007)
Memo from Fred Panzer to Anne Girolamo requesting the development of charts to inform legislators on the tobacco industry's position regarding federal tax rates over eight cents. Asks for a chart on the negative economic effects of such a tax increase and a chart portraying the inconsequentially small impact such a tax would have on the federal budget. Includes sample graphs and tables.